2008
DOI: 10.2108/zsj.25.146
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Population Structure of the White-Spotted Charr (Salvelinus leucomaenis) in the Lake Biwa Water System

Abstract: A phylogeographic analysis of mitochondrial DNA sequences was performed in order to elucidate the origin, dispersal process, and genetic structure of white-spotted charr in the Lake Biwa water system. Two haplotypes were most common in the Lake Biwa water system, and were also common in the adjacent inlet rivers of the Sea of Japan. These results suggest that in the glacial periods of the Pleistocene, white-spotted charr dispersed into the northern inlet rivers of Lake Biwa from adjacent inlet rivers of the Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…On the other hand, it has been reported that the mean annual temperature in Japan from 7,000 to 5,000 years ago was higher by 1-2°C than the current temperature (Yasuda 1997). This postglacial warming might have reduced the habitat size of white-spotted charr populations, and the level of habitat reduction would be higher in the western Lake Biwa populations than the eastern due to the smaller high altitude area (Kikko et al 2008c). Thus, the correlation between haplotype diversity and census population size in the eastern part of the system and monomorphic haplotype diversity in the western part of the system could be due to the different levels of bottlenecks related to the habitat size between the eastern and western parts of the system during the warmer postglacial period than today, although it appears to result partly from historical incidents such as range expansion as well as recent anthropogenic disturbances.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, it has been reported that the mean annual temperature in Japan from 7,000 to 5,000 years ago was higher by 1-2°C than the current temperature (Yasuda 1997). This postglacial warming might have reduced the habitat size of white-spotted charr populations, and the level of habitat reduction would be higher in the western Lake Biwa populations than the eastern due to the smaller high altitude area (Kikko et al 2008c). Thus, the correlation between haplotype diversity and census population size in the eastern part of the system and monomorphic haplotype diversity in the western part of the system could be due to the different levels of bottlenecks related to the habitat size between the eastern and western parts of the system during the warmer postglacial period than today, although it appears to result partly from historical incidents such as range expansion as well as recent anthropogenic disturbances.…”
Section: Resultsmentioning
confidence: 96%
“…These results suggest that the low haplotype diversity of the western populations is mainly explained by historical bottlenecks rather than current reduction in population size. White-spotted charr populations in the Lake Biwa water system might have maintained the genetic variability at a similar level between the western and eastern parts until the end of the last glacial period because of the gene flow among the populations through the littoral waters of Lake Biwa (Yamamoto et al 2004a, b;Kikko et al 2008c). The current tributary length (a proxy for potential habitat size) populated by white-spotted charr between the eastern and western parts of the system were not significantly different (mean ± SD = 1,588 ± 1,273 m in the eastern part; 1,040 ± 594 m in the western part; Mann-Whitney U test, U = 4.0, P [ 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations